2002
DOI: 10.1177/001041402236310
|View full text |Cite
|
Sign up to set email alerts
|

Does Left/Right Structure Party Positions on European Integration?

Abstract: How is contestation on European integration structured among national political parties? Are issues arising from European integration assimilated into existing dimensions of domestic contestation? We show that there is a strong relationship between the conventional left/right dimension and party positioning on European integration. However, the most powerful source of variation in party support is the new politics dimension, ranging from Green/alternative/libertarian to Traditional/authoritarian/nationalist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
729
3
22

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,163 publications
(805 citation statements)
references
References 41 publications
21
729
3
22
Order By: Relevance
“…In earlier stages of the European project, as most political parties converged toward an EU-positive position, the EU dimension was far less salient to domestic and European electoral competition (Hooghe et al, 2002). In this context, previous research found that attitudes towards the EU were at best weak predictors of electoral behaviour in EP elections (de Vries and Hobolt, 2012;Hobolt and Wittrock, 2011).…”
Section: European-level Versus National Political Competitionmentioning
confidence: 91%
“…In earlier stages of the European project, as most political parties converged toward an EU-positive position, the EU dimension was far less salient to domestic and European electoral competition (Hooghe et al, 2002). In this context, previous research found that attitudes towards the EU were at best weak predictors of electoral behaviour in EP elections (de Vries and Hobolt, 2012;Hobolt and Wittrock, 2011).…”
Section: European-level Versus National Political Competitionmentioning
confidence: 91%
“…Therefore news coverage in the media used by a voter of a party's stances on the leftright dimension is expected to increase that voter's likelihood to vote for that party. The same is expected to hold for news about the cultural GALTAN dimension (Hooghe, Marks, & Wilson, 2002;Kriesi et al, 2006Kriesi et al, , 2008, although the latter is more often debated (Van der Brug & Van Spanje, 2009).…”
Section: Electoral Consequences Of Party Emphasis On Old Issue Dimensmentioning
confidence: 92%
“…The significant logistic regression coefficients show that reports in the media used by voter about party positioning on the left-right dimension (H2a) and on the cultural dimension (H2b) increase the likelihood to vote for these parties. The most likely underlying mechanism is that voters will reward parties who succeed in getting media coverage for their owned issues, which are usually either left or right (Budge & Farlie, 1983), or either Green, Alternative and Libertarian or Traditional, Authoritarian and Nationalist (Hooghe et al, 2002). Because national parties are not portrayed as powerful players in EU news, we expected a negative effect on the vote of the news about parties addressing the EU, the euro crisis, or the Ukraine conflict.…”
Section: Effects Of Political Newsmentioning
confidence: 99%
“…Heath et al (1994) refer to this scale as Socialist/laisez faire, we deem this confusing and changed it to the more commonly used economic left-right dimension (e.g. Hooghe, Marks, & Wilson, 2002). 2.…”
Section: Notesmentioning
confidence: 99%